358 The short and long term effects of weaning on structural and transcriptomic adaptations of the colon in Holstein bull calves fed elevated plane of milk nutrition pre-weaning. (7th December 2018) - Van Niekerk, J; Romao, J; Middeldorp, M; Steele, M
Abstract: This study aimed at assessing the impact of weaning on the histological structure and transcriptome of the colon from six Holstein dairy bull calves fed an elevated plane of milk nutrition pre-weaning. Calves were fed milk replacer solution (5.1 Mcal/kg; 150 g/L) at 15% of body weight and milk volumes were adjusted weekly according to body weight. Calves were weaned by reducing milk allocation by 50% during wk 6. Calf starter, chopped straw and water were offered ad libitum. Colonic endoscopic biopsies were performed to collect tissue samples for histological measurements (week 5, 6, 7, 8 and 12) which revealed that the mucosa layer of the colon tended to be decreased (P = 0.07) week 7 compared with week 5 and was significantly decreased (P = 0.01) week 8 compared with week 5. Transcriptomic analysis was performed on biopsy samples at week 5, 7 and 12. The analyses uncovered 86 genes (23 up and 63 down) were differentially expressed (DE) during the short term adaptation (week 5 to 7) while 436 genes (190 up and 246 down) were DE during long term adaptation (week 5 to 12), based on a false discovery rate (FDR) of 0.1. Ingenuity Pathway Analysis (IPA) revealed that Cell Death and Survival functions were more activated during the short term adaptation such as necrosis (z-score = 3.156). The long term adaptation displayed higher activation of functions related to Cellular Movement and Cellular and Tissue Development such as cell movement (z-score = 2.722), proliferation of epithelial cells (z-score = 1.892) and proliferation of enterocytes (z-score = 1.982). These results indicate that weaning negatively impacts cell survival of the colon during short term adaptation and that it takes several weeks after weaning for functions involved in Cellular Development and Proliferation in the colon to have higher activation.